Breakthrough Branding : Positioning Your Library to Survive and Thrive. - Walters, Suzanne (American Library Association, 2014)
Breakthrough Branding: Positioning Your Library to Survive and Thrive shows how to mesh your library's brand deeply and seamlessly within your internal culture, to leverage and better position your brand for the audiences you serve, and develop and implement promotional strategies and tactics consistent with your objectives.